1991
DOI: 10.1002/syn.890080402
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of mu‐ and delta‐receptor selective opioid agonists on feedforward and feedback GABAergic inhibition in hippocampal brain slices

Abstract: Previous studies have suggested that opioid receptor activation in the hippocampus increases pyramidal neuron excitability by reducing GABAergic inhibition. This hypothesis has received support with regard to mu-receptor agonists but has not been adequately tested with selective delta-receptor agonists. In the present investigation we compared the effects of the selective mu-opioid receptor agonist [Tyr-(D-Ala)-Gly-(N-Me-Phe)-Gly-ol]-enkephalin (DAGO) and the delta-receptor agonist [D-Pen2,D-Pen5]-enkephalin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…Whereas opioids strongly increase hippocampal excitability and can induce epileptic activity (Lee et al, 1989;Lupica and Dunwiddie, 1991), cannabinoids subtly disrupt the timing without changing the overall rate of activity (Paton et al, 1998;Robbe et al, 2006). This suggests that opioids and cannabinoids affect inhibitory systems in a different manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas opioids strongly increase hippocampal excitability and can induce epileptic activity (Lee et al, 1989;Lupica and Dunwiddie, 1991), cannabinoids subtly disrupt the timing without changing the overall rate of activity (Paton et al, 1998;Robbe et al, 2006). This suggests that opioids and cannabinoids affect inhibitory systems in a different manner.…”
Section: Discussionmentioning
confidence: 99%
“…The selective modulation of feedback inhibition by cannabinoids will increase the tendency of pyramidal cells to burst (Robbe et al, 2006) and disrupt oscillatory activity (Hajos et al, 2000). In contrast, because opioids selectively modulate feedforward inhibition, they will increase the spiking probability in response to afferent excitation, increase the integration time window, and decrease the synchrony of hippocampal pyramidal cells (Lupica and Dunwiddie, 1991;Pouille and Scanziani, 2001). Given that opioids increase the excitability of pyramidal cells, we were surprised that the amplitude of feedback inhibition did not increase in the presence of DAMGO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the effects of MOR activity in hippocampal CA1 were proposed to act through effects on inhibitory interneurons (Lupica and Dunwiddie 1991), the effects of MOR activation on excitatory activity in CA1 should be occluded in the absence of synaptic inhibition. This hypothesis was tested by blocking GABA B receptors with CGP 55845 and then examining the effect of DAMGO in complete suppression of GABA receptor function.…”
Section: Suppression Of Gaba Receptors Occludes the Effects Of Mop Rementioning
confidence: 99%
“…In support of a mechanism of action for MOR activation within the dendrites of CA1 pyramidal cells, voltage-sensitive dye (VSD) studies showed that MOR activation can enhance paired-pulse excitatory activity within the dendrites of CA1 pyramidal neurons and that this enhancement was the result of an inhibition of ␥-aminobutyric acid type A (GABA A ) IPSPs (McQuiston and Saggau 2003). However, MOR activation in CA1 pyramidal cells was also shown to inhibit GABA B IPSPs (Lupica and Dunwiddie 1991), but the site of action for MOR effects on GABA B synaptic inhibition along the somatodendritic domain of CA1 pyramidal cells has not been examined. Therefore in an effort to determine the anatomical location of MOR suppression of GABA B synaptic function in hippocampal CA1, we isolated GABA B synaptic function from GABA A synaptic activity with bicuculline (50 M) and used VSD imaging to simultaneously measure changes in inhibitory and excitatory synaptic events in all layers of CA1 after the application of the MOR agonist DAMGO.…”
Section: Introductionmentioning
confidence: 99%